2023
DOI: 10.1002/jpen.2550
|View full text |Cite|
|
Sign up to set email alerts
|

Guidelines for parenteral nutrition in preterm infants: The American Society for Parenteral and Enteral Nutrition

Daniel T. Robinson,
Kara L. Calkins,
Yimin Chen
et al.

Abstract: BackgroundParenteral nutrition (PN) is prescribed for preterm infants until nutrition needs are met via the enteral route, but unanswered questions remain regarding PN best practices in this population.MethodsAn interdisciplinary committee was assembled to answer 12 questions concerning the provision of PN to preterm infants. The Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) process was used. Questions addressed parenteral macronutrient doses, lipid injectable emulsion (ILE) compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 69 publications
2
15
0
Order By: Relevance
“…Many of these NICUs lack sufficient facilities and staff that care for preterm infants. The most recent European and US guidelines recommended that PN should be initiated early, within the first one to two hours of life in preterm infants [ 9 , 10 , 16 , 17 ], and our survey results reported a high level of compliance.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Many of these NICUs lack sufficient facilities and staff that care for preterm infants. The most recent European and US guidelines recommended that PN should be initiated early, within the first one to two hours of life in preterm infants [ 9 , 10 , 16 , 17 ], and our survey results reported a high level of compliance.…”
Section: Discussionsupporting
confidence: 61%
“…Our survey revealed that the initial dose of AA ranged from 1 to 2 g/kg/day in 85.6% (89 out of 104) NICUs. For the maximum dose of AA, this varies in previous clinical trials, from 2.5 to 4.5 g/kg/day [ 17 ]. Current evidence also shows limited difference in clinical outcomes between a maximum AA dose of 3.5 versus 4 g/kg/day [ 5 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey documented that 85.6% (89 out of 104) of NICUs provided amino acids (AA) within 24 hours of life (on the PN was initiated), consistent with existing guidelines [9,10,[16][17][18]. Still, the remaining NICUs (14.4%) deferred providing AA.…”
mentioning
confidence: 67%
“…To the Editor, We welcomed the American Society for Parenteral and Enteral Nutrition guidelines for parenteral nutrition (PN) in preterm infants, 1 but were surprised to find a recommendation on restriction of amino acids (AAs) based on an increased risk of sepsis. We are writing to express our concerns regarding the authors' interpretation of the data, which led to a recommendation that has the potential to alter practice significantly.…”
mentioning
confidence: 99%